Simulation of Poyang Lake water levels and outflow under historical extreme hydrological scenarios. Issue 3 (13th April 2022) - Yu, Meixiu; Liu, Xiaolong; Wood, Paul; Wei, Li; Wang, Guoqing; Zhang, Jianyun; Li, Qiongfang
Abstract: Due to an intensification of anthropogenic activities and climate change in recent decades, the hydrological connections and relationships between rivers and lakes have been significantly modified globally. Poyang Lake is one of the largest freshwater lakes globally and is one of the few that remain naturally connected to the Yangtze River. To investigate the full hydrological conditions (extreme high and low discharge) of Poyang Lake outflow under current bathymetric conditions, a large‐scale 1D‐ and 2D‐coupled high‐resolution hydrodynamic model of the Poyang Lake basin–Yangtze River system was developed. We simulated the outflow and water levels of Poyang Lake under nine different extreme hydrological scenarios with high precision and computational efficiency. We propose (1) a novel partition calibration method to characterize the roughness coefficient of large water bodies in complicated geographical terrain both for wet and dry seasons; (2) a new method for setting initial conditions for hydrodynamic simulation of large water bodies subject to strong hydrological regulation. Results indicated that (1) maximum outflow and water levels will reach 37, 200 m 3 /s and 22.28 m when Poyang Lake basin floodwater coincides with flooding on the Yangtze River; (2) precipitation over the lake has increased outflow but this has had very limited influence on its changing hydrological pattern; (3) the effect of hydrological conditions within the system differs for both the lake outflow and water level. The research provides important reference conditions for the application of the InfoWorks ICM model in future applications and studies of large river–lake systems.